Overview of past, current, and future ecosystem and biodiversity trends of inland saline lakes of Europe and Central Asia. Issue 4 (1st October 2020) - Zadereev, Egor; Lipka, Oksana; Karimov, Bakhtiyor; Krylenko, Marina; Elias, Victoria; Pinto, Isabel Sousa; Alizade, Valida; Anker, Yaakov; Feest, Alan; Kuznetsova, Daria; Mader, Andre; Salimov, Rashad; et al.
ABSTRACT: This review of trends in inland saline lakes of Europe and Central Asia is based on the relevant section of the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES) Regional Assessment Report for Europe and Central Asia (ECA). We assessed the present status of ECA saline lakes and the effects of direct drivers (climate change, land use, pollution, resource exploitation, invasive species) on ecosystem health and biodiversity. We also assessed past, current and future trends using habitat area and degradation, species richness, and endangered species as indicators. No uniform scenario is applicable to saline lakes in the region. The desiccation of the Aral Sea is caused mainly by land use change and water extraction. In the Caspian Sea, river modifications, water pollution, overfishing and poaching, and species invasions have led to a decrease in species richness and have threatened endemic species. Although trends for smaller saline lakes vary, our analysis demonstrates that land use change, over-exploitation, and pollution are more important direct drivers of ecosystem health and biodiversity than climate change. The establishment of baseline biodiversity values for saline lakes is, however, complicated because biodiversity and the food-web structure are variable and depend strongly on salinity. Thus, there is a need to classify the ecological quality, biodiversity and ecosystem services of saline lakes along a salinity gradient. The improvement of water management and reuse of water, conservation measures, and introduction of climate-smart agriculture are basic conditions for the sustainable use of saline lakes in the region.